Recovery and application of chitosan from Sabah shrimp shell waste through deacetylation of chitin at different parameters - Flornica Alca Ahing (2018)
The comparison between head shell and body shell was carried out to determine the best option to be used in this study. Besides that, the deacetylation of chitin at different parameters were also investigated which including soaking frequency, temperature and time treatment factor, to recover chitosan. This study was performed by soaking frequency once and twice, temperatures at 50°C, 60°C, 70°C and 80°C, and time treatment 12, 24, 36 and 48 hours while the characterization of chitosan was determined in terms of moisture content, ash value, solubility and degree of deacetylation. Besides that, a preliminary investigation was carried out to study the effect of chitosan in tilapia fish feed towards growth and survival rate by using 1.00%, 2.00% and 3.00% chitosan. The results obtained in this study shows that the body shell was a better option to produce chitosan as it produces higher chitosan yield compare to head which were 13.35% and 7.27%, respectively. In the meantime, deacetylation process at room temperature for twice soaking gave a higher degree of deacetylation value and solubility compare to once which were 75.24% and 88.57%, while the solubility were 97.78% and 98.32%, respectively. Furthermore, the moisture content and ash value of the chitosan produced in this study ranged from 4.27% to 9.19% and 0.22% to 0.90%, respectively. In addition, deacetylation process carried out at temperature 70°C and time treatment 48 hour gave the highest solubility and degree of deacetylation which was 97 .00% and 90.96%, respectively. For the meantime, the application of chitosan-supplemented fish feed on tilapia suggests that 1.00% chitosan increased the highest fish weight with 142.80%, while the 3.00% chitosan increased the length with 48.74%. The survival rate of tilapia fish was also observed to be 100% when 1.00% and 2.00% chitosan were used as the feed, compared to control with 63.00% only. Thus, this study demonstrated temperature and time treatment factors play a crucial role in recovering a good solubility and degree of deacetylation quality of chitosan. Chitosan produced in this study was also high in quality with 90.96% of degree of deacetylation, which can be used in industry that need further investigation for different application.